2015
DOI: 10.1016/j.socscimed.2015.09.007
|View full text |Cite|
|
Sign up to set email alerts
|

How reliable are self-reports of HIV status disclosure? Evidence from couples in Malawi

Abstract: Introduction The majority of research on human immunodeficiency virus (HIV) disclosure utilizes the perspective from a single individual, which cannot be substantiated in the absence of supporting data such as from a primary partner. Objectives The objectives of this study were to evaluate: (1) the extent to which self-reported HIV disclosure was confirmed by a primary partner; (2) individual and relationship-level predictors of self-reported versus confirmed disclosure; and (3) whether confirmed disclosure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 42 publications
1
11
0
1
Order By: Relevance
“…Of the 89 couples included in the present study, 70 (79%) agreed that they had both received an HIV test and disclosed their results. Rates of HIV testing were similarly high in a previous study in rural southern Malawi which found that in 87% of couples both partners reported that they had been tested for HIV and disclosed to their partners [ 35 ].…”
Section: Discussionmentioning
confidence: 76%
“…Of the 89 couples included in the present study, 70 (79%) agreed that they had both received an HIV test and disclosed their results. Rates of HIV testing were similarly high in a previous study in rural southern Malawi which found that in 87% of couples both partners reported that they had been tested for HIV and disclosed to their partners [ 35 ].…”
Section: Discussionmentioning
confidence: 76%
“…As such, positive relationship dynamics (e.g., intimacy, trust) enhance couples’ capacity for successful coordination of health behaviors, while negative relationship dynamics (e.g., IPV) make it difficult for couples to work together. In South Africa and Malawi, relationship dynamics such as commitment, unity, equality, trust, and communication have been linked to increased HIV testing and disclosure in couples (Darbes, Dladla, and Mogale 2006, Conroy 2014a, b, van Rooyen et al 2014, Conroy and Wong 2015). Less is known about the intersection between relationship dynamics and adherence in sub-Saharan Africa; however; evidence from resource-rich settings suggests that higher relationship quality is positively associated with ART adherence and virologic control (Knowlton et al 2011, Johnson et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the results could be biased by the increased participation of higher-functioning couples who stayed together over the study period—which has been noted as a limitation in other couples studies on primary relationships (15, 63). However, our modeling approach was robust enough to account for missing data under the relatively mild MAR assumption and made use of all data available from participants at each visit, which would enhance generalizability.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is evidence to suggest that partner beliefs about viral load could be inaccurate. Studies on heterosexual couples conducted outside of the U.S. have found that perceptions of a partner's HIV status and actual serostatus are often mismatched (12) and that there can be discrepancies between partners about whether HIV status disclosure has occurred (13-15). Yet, little research, if any, has examined the accuracy of partner beliefs about viral suppression and whether these beliefs change as treatment and relationship trajectories evolve over time.…”
Section: Introductionmentioning
confidence: 99%